Islamic Finance-Growth Nexus: Evidence from Malaysia - Kazak, Hasan; Okka, Osman (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
For many years, a plethora of theoretical and empirical studies have illustrated the relationship between financial activities and economic growth. The impact of the Islamic financial system and its instruments on economic growth has begun to emerge in recent years, parallel with its development. This study is designed to contribute to the development of Islamic finance as well as contribute to the literature by revealing the causal relationship between the development of Islamic finance and economic growth. To serve this purpose, an examination in the context of Malaysia, which has progressed more than other countries in terms of Islamic financial development, has been carried out. In exploring the causal relationship between the development of Islamic finance and economic growth in Malaysia, four variables representing Islamic banking, Sukuk market, and Islamic stock market on the gross domestic product (GDP) are discussed through data from the first quarter of 2006 to the first quarter of 2020. To analyze the relationship of the variables within the framework of the VAR model, the Johansen cointegration test, impulse-response functions, and variance decomposition was used. This study corroborates the literature on the effect of the financial sector development on economic growth by taking Islamic finance into account.